Crash performance of polyurethane foam-filled aluminium column - Nurul Izzah, Ab Rahim (2020)
For an ideal impact energy absorber, the initial peak force (IPF) should be minimized but energy absorption (EA) and specific energy absorption (SEA) should be maximized. Application of the thin-walled tube as energy absorber under axial loading condition produces controlled progressive collapse during the crushing process which is a desirable collapse mechanism. However, the conventional thin-walled tubes produce high initial peak force and fluctuations during the crushing process. The existing foam-filled design has been succeeded in stabilising the fluctuation and increase the SEA but the initial peak force is increased simultaneously. The aim of this study is to decrease the initial peak force and optimise the specific energy absorption. This study has been carried out to improve the performance of energy-absorbing structure by using a partially foam-filled structure with a few variations in foam length. The entire crushing performance of the specimen has been investigated by experiment. This proposed partially foam-filled structure design using 3 different length of foam which is 195 mm, 190 mm and 185 mm that filled in the square aluminium column. The experimental results showed that the reduction of foam length has affected the initial peak force of the structure and energy absorption capacity. Under quasi-static test, reduction in foam length to 195 mm has decreased the IPF to 23% by decreasing only 1% in SEA compared to full-filled (A1.4P200) specimen for 1.4 mm thickness structure. For specimen with 2.0 mm thickness, the IPF and SEA were decreased by 3% and 24% respectively compared to full-filled (A2.0P200) specimen. While under impact test, specimen with 1.4 mm thickness and length of foam 190 mm shown the best performance by reducing the IPF by 31% while reduced only 6% of the SEA. For 2 mm thickness specimen, the IPF was reducing with the reduction in length of foam but the SEA was constant for all specimen. The new design which using the partly foam-filled, is proved to reduce the IPF and optimise the SEA of the structure. Finally, the optimization method using response surface method has shown that for the quasi-static test, the best solution gained by the length of foam of 195 mm with the thickness of 1.74 mm that produces the value for IPF of 70 kN and SEA of 1.7 kJ/kg while for impact test the best solution gained by length of foam of 195 mm with the thickness of 1.46 mm that produce the value of IPF for 103 kN and SEA of 1.5 kJ/kg.